Sequential Treatment Escalation with Dapagliflozin and Saxagliptin Improves Beta Cell Function in Type 2 Diabetic Patients on Previous Metformin Treatment: An Exploratory Mechanistic Study - Forst, Thomas; Alghdban, Mohammed Khaled; Fischer, Annelie; Weber, Matthias M.; Voswinkel, Stephan; Heise, Tim; Kapitza, Christoph; Plum-Mörschel, Leona (Hormone and Metabolic Research, 2018)
We investigated the effect of sequential treatment escalation with dapagliflozin and saxagliptin on beta cell function in patients with T2DM insufficiently controlled on metformin monotherapy during a hyperglycaemic clamp investigation. Twenty-six patients (19 males, age 63.5±7.0 years; duration of diabetes 8.8±4.7 years; HbA1c 63.9±15.8 mmol/mol; mean±SD) were enrolled in the study. During a first treatment period (TP1) all patients received 10 mg dapagliflozin for one month, followed by the addition of 5 mg saxagliptin or placebo for another month (TP2). At baseline and at the end of each treatment period, fasting glucose and insulin levels were analysed, and a hyperglycaemic clamp with the measurement of plasma C-peptide, insulin, proinsulin, and glucagon was performed. Treatment with dapagliflozin reduced fasting glucose levels and insulin resistance (TP1). Within the hyperglycaemic clamp, C-peptide and insulin concentrations increased after the addition of dapagliflozin in TP1 (0.48±0.45 nmol*h/l; 6.24±17.9 mU*h/l) and further improved after the addition of saxagliptin in TP2 (0.38±0.34 nmol*h/l; 6.59±10.15 mU*h/l). Acute insulin response did not change after the addition of dapagliflozin (TP1), but significantly improved after the addition of saxagliptin in TP2 (0.89±0.76 mU*h/l). Both drugs improved the C-peptide/proinsulin ratio. After the addition of saxagliptin, the glucagon/insulin ratio significantly declined (TP2). Treatment escalation with dapagliflozin and saxagliptin exhibit additive effects on beta cell capacity, and improves alpha and beta cell integrity.
Keywords: beta cell function; hyperglycaemic clamp; SGLT-2 inhibition; DPP-IV inhibition